Developing social and emotional skills through play: study of a programme inspired by the CASEL model in Year 5 - Zainab Talhata; Rajae Achiq (International Journal of Scientific Research and Innovative Studies, 2026)
This study investigates the impact of play on the development of social and emotional competencies among two groups of 4th-grade students (CM1). The study is based on the implementation of an experimental program, Ludo-SEL, which offers structured play-based activities designed around the five core competencies of the CASEL framework (self-awareness, self-management, social awareness, relationship skills, and responsible decision-making). Recognized internationally, the CASEL model provides a solid theoretical foundation for the integration of Social and Emotional Learning (SEL) into educational practices. Through an analytical and comparative methodology, the results highlight the positive effects of the program on several socio-emotional skills, particularly emotional regulation and the quality of peer interactions. This research thus underlines the relevance of play as a pedagogical tool, capable of enhancing student engagement and supporting holistic development. It encourages a rethinking of education through a more human, inclusive, and trans- versal approach, placing emotional well-being at the heart of the learning process. Keywords: Social and Emotional Learning (SEL), play-based learning, CASEL framework emotional regulation, socio-emotional competencies, primary education. Received Date: December 20, 2025 Accepted Date: January 12, 2026 Published Date: February 01, 2026 Available Online at: https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/561